Hepatitis C Virus (HCV)–Apolipoprotein Interactions and Immune Evasion and Their Impact on HCV Vaccine Design - Wrensch, Florian; Crouchet, Emilie; Ligat, Gaetan; Zeisel, Mirjam B.; Keck, Zhen-Yong; Foung, Steven K. H.; Schuster, Catherine; Baumert, Thomas F. (Frontiers in Immunology, 2018)
With more than 71 million people chronically infected, hepatitis C virus (HCV) is one of the leading causes of liver disease and hepatocellular carcinoma. While efficient antiviral therapies have entered clinical standard-of-care, the development of a protective vaccine is still elusive. Recent studies have shown that the HCV life cycle is closely linked to lipid metabolism. HCV virions associate with hepatocyte-derived lipoproteins to form infectious hybrid particles that have been termed lipo-viro-particles. The close association with lipoproteins is not only critical for virus entry and assembly but also plays an important role during viral pathogenesis and for viral evasion from neutralizing antibodies. In this review, we summarize recent findings on the functional role of apolipoproteins for HCV entry and assembly. Furthermore, we highlight the impact of HCV-apolipoprotein interactions for evasion from neutralizing antibodies and discuss the consequences for antiviral therapy and vaccine design. Understanding these interactions offers novel strategies for the development of an urgently needed protective vaccine.